Use of biodiversity hotspots for conservation of Marine Molluscs: a regional approach - BEDULLI, D.; BASSIGNANI, F.; BRUSCHI, A. (Mediterranean Marine Science, 2002)
A method to define biodiversity hot spots as regards marine molluscs is proposed. Species richness of Italian marine molluscs is analysed by means of data collected by members of the Italian Malacological Society. Data are ordered in the database ‘Census of Italian Marine Molluscs’ available on the Internet. The Census contains about 20.000 records concerning 901 species sampled in 663 localities around all the Italian coasts. The records are divided into 59 lots; for each lot we formulate an index of species richness not related to the sampling effort. This index shows a positive correlation with the environmental diversity and with the proportion of hard substrates on the sea bottom. In the lots we assess the distribution of species worth of protection (according to literature) and of most rare species. Combining these data with the distribution of lots with higher values of species richness index, we identify hot spots available for conservation.